SOSIALISASI KOMPETENSI GURU DAN PENGGUNAAN MASALAH KONTEKSTUAL DALAM PEMBELAJARAN DI LEMBAGA PENDIDIKAN AL-MA’ARIF KUNINGAN - Riza Fatimah Zahrah; Fajar Nugraha; Hatma Heris Mahendra; Dudung Suryana (Journal of Empowerment Community, 2020)
Tumenggung Argawijaya foundation care to the education sector especially of basic education .Under a shade foundation tumenggung argawijaya standing as many as the three institutions such as Early childhood education, Islamic Diniyyah. An educational institution Al-Ma’arif  let encounters many obstacles such as the aspect of human resources that is the motivation , innovation and creativity is still low which is potential to the process of teaching in which you held the realization of education and .Repair the aspect of human resources in improved the motivation of done with information competence that should be owned by an educator.The event was held by about to transfer of competence that should be owned by an educator for one day. Then to increase innovation and creativity human resources activities are transferring technologies regarding the use of contextual problems for one day and assistance in the process of learning for one day. A method of execution that used on an activity pkm it encompasses a method of transfer technology and sustainable assistance of an implementation team to gradually. partnerThe conclusion of its service that the satisfaction of the partners for the implementation of this activity due to lack of guidance from the government against teachers in an educational institution Al-Ma’arif